2021
DOI: 10.3390/ijms23010135
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Mitochondrial-DNA-Driven Inflammation Pathways on Macrophage Polarization: A New Perspective for Targeted Immunometabolic Therapy in Cerebral Ischemia-Reperfusion Injury

Abstract: Cerebral ischemia-reperfusion injury is related to inflammation driven by free mitochondrial DNA. At the same time, the pro-inflammatory activation of macrophages, that is, polarization in the M1 direction, aggravates the cycle of inflammatory damage. They promote each other and eventually transform macrophages/microglia into neurotoxic macrophages by improving macrophage glycolysis, transforming arginine metabolism, and controlling fatty acid synthesis. Therefore, we propose targeting the mtDNA-driven inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 171 publications
0
7
0
Order By: Relevance
“…This is the first report on the effect of GL on improving glucose uptake after cerebral ischemia. Recent research has shown [ 31 ] that improvements in the energy utilization status of brain tissue can modulate the polarization of microglia. M1 microglia are activated by canonical activation pathway LPS/IFN- γ , and their main metabolic pathways are anaerobic glycolysis and pentose phosphate, whilst M2 microglia are activated by IL-4/IL-13 and have an intact tricarboxylic acid (TCA) cycle and oxidative phosphorylation (OXPHOS) process with prominent fatty acid synthesis and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report on the effect of GL on improving glucose uptake after cerebral ischemia. Recent research has shown [ 31 ] that improvements in the energy utilization status of brain tissue can modulate the polarization of microglia. M1 microglia are activated by canonical activation pathway LPS/IFN- γ , and their main metabolic pathways are anaerobic glycolysis and pentose phosphate, whilst M2 microglia are activated by IL-4/IL-13 and have an intact tricarboxylic acid (TCA) cycle and oxidative phosphorylation (OXPHOS) process with prominent fatty acid synthesis and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Various metabolic processes are associated with cerebral ischemia-reperfusion injury-induced brain tissue damage [43][44][45] . Therefore, we estimated the metabolic status of various cell compositions in different groups based on their expression pro les.…”
Section: Lrg1 Knockout Alters the Metabolic Status Of Multiple Cell P...mentioning
confidence: 99%
“…Mitochondrial DNA oxidation is considered another requirement for inflammasome activation; although more recent evidence has refuted the above hypothesis considering that both mtROS and mitochondrial dysfunction do not appear to be indispensable in determining the phlogistic activation of inflammasome [ 78 ].…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%